SUSTENTABILIDADE E RESPONSABILIDADE SOCIAL CORPORATIVA: UMA REFLEXÃO SOBRE A NECESSIDADE DE EVOLUÇÃO DAS PRÁTICAS EMPRESARIAIS - Albejante, Lia Mazon (2009)
This study has the general objetive of raising a debate on the need for changes in business practices, taking into account the context of sustainability and corporate social responsibility. Its specific objectives are to investigate: studies on the evolution of consciousness and macroshift; concepts of sustainability and corporate social responsibility; theories that propose the transformation of people management; and theories on prospective scenarios. An exploratory research was used, based on a bibliografic reaserch in a qualitative approach. The bibliographic research was based on authors that bring a reflection about the current context, in which organizations are inserted. Consequently, the necessity of a change is remarked. Furthermore, this study shows the importance of the companies s role during this changing process, among coherent practices with sustainability and corporate social responsibility. It is also based on the literature about prospective scenarios as motivator of the need of reflection about the future and its construction. From the results of this study, it s possible to see the enormous amount of scientific work being devoted to topics related to the role of business in society. It can be concluded that the evolution of society when thought from the business environment, requires necessarily people management and sustainability and corporate social responsibility.